Globalization and Orthodox Christianity: the transformations of a religious tradition - Roudometof, Victor (Routledge studies in religion, 2014)
"With approximately 200 to 300 million adherents worldwide, Orthodox Christianity is among the largest branches of Christianity, yet it remains relatively understudied. This book examines the rich and complex entanglements between Orthodox Christianity and globalization, offering a substantive contribution to the relationship between religion and globalization, as well as the relationship between Orthodox Christianity and the sociology of religion and more broadly, the interdisciplinary field of Religious Studies. While deeply engaged with history, this book does not simply narrate the history of Orthodox Christianity as a world religion, nor does it address theological issues or cover all the individual trajectories of each subgroup or subdivision of the faith. Orthodox Christianity is the object of the analysis, but author Victor Roudometof speaks to a broader audience interested in culture, religion, and globalization. Roudometof argues in favor of using globalization instead of modernization as the main theoretical vehicle for analyzing religion, displacing secularization in order to argue for multiple hybridizations of religion as a suitable strategy for analyzing religious phenomena. It offers Orthodox Christianity as a test case that illustrates the presence of historically specific but theoretically distinct glocalizations, applicable to all faiths. "--